2010
DOI: 10.1074/jbc.m109.067207
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 Mediates Antiapoptotic Effect by Phosphorylating Bad through a β-Arrestin 1-mediated ERK1/2 Activation in Pancreatic β-Cells

Abstract: Strategies based on activating GLP-1 receptor (GLP-1R) are intensively developed for the treatment of type 2 diabetes. The exhaustive knowledge of the signaling pathways linked to activated GLP-1R within the ␤-cells is of major importance. In ␤-cells, GLP-1 activates the ERK1/2 cascade by diverse pathways dependent on either G␣ s /cAMP/cAMP-dependent protein kinase (PKA) or ␤-arrestin 1, a scaffold protein. Using pharmacological inhibitors, ␤-arrestin 1 small interfering RNA, and islets isolated from ␤-arresti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
132
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(145 citation statements)
references
References 69 publications
9
132
1
2
Order By: Relevance
“…Our findings are consistent with a previous report showing that Glp1r activation attenuates hyperglycemia-induced apoptosis in pancreatic islet microendothelial cells (13). Antiapoptotic functions of Glp1r activation have been attributed to increases in Bcl-2 (6) and Bad phosphorylation (37) and decreases in Bax expression (36) and caspase 3 activity (54). Consistent with these observations, we show that Glp1r activation prevents high glucose-induced caspase 3 activity.…”
Section: Discussionsupporting
confidence: 82%
“…Our findings are consistent with a previous report showing that Glp1r activation attenuates hyperglycemia-induced apoptosis in pancreatic islet microendothelial cells (13). Antiapoptotic functions of Glp1r activation have been attributed to increases in Bcl-2 (6) and Bad phosphorylation (37) and decreases in Bax expression (36) and caspase 3 activity (54). Consistent with these observations, we show that Glp1r activation prevents high glucose-induced caspase 3 activity.…”
Section: Discussionsupporting
confidence: 82%
“…In addition to inducing CREB phosphorylation, β-adrenergic agonism also activates Akt and extracellular signal-related kinase (ERK) [5,17,18]. In contrast to the two phases of ERK activation by glucagonlike peptide 1 in the pancreatic beta cells, ERK activation induced by isoprenaline treatment in TGP52 cells is monophasic [19]. Akt phosphorylation in our study, however, showed no significant change (Fig.…”
Section: /β2arcontrasting
confidence: 51%
“…New studies have revealed that β-arrestin 1 is a major downstream mediator of GPCRs, such as β2AR, GLP-1R, M3R and A1TaR, and is involved in genome stability, pancreatic beta cell function, podocyte activation and renal injury [5,19,35,36]. However, the functional importance of β-arrestin 1 in pancreatic delta cells had not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…They are able to coordinate almost limitless combinations of protein complexes, which accounts for their functional diversity [3][4][5]26]. A previous report established that one isoform is present in beta cells [41], but without an in-depth investigation of its physiological function. In the present study, inhibition of 14-3-3 function with difopein or a cell-permeable inhibitor promoted cell death, but the differential regulation of isoform levels by cellular stressors Fig.…”
Section: Discussionmentioning
confidence: 99%